Hands-On Full Stack Development with Go : Build Full Stack Web Applications with Go, React, Gin, and GopherJS. - Andrawos, Mina (Packt Publishing Ltd, 2019)
Go programming has been rapidly adopted by developers for building web applications. With its ecosystem growing in size and its stable architecture, Go offers a library for building scalable and high-performant web services and apps. Hands-On Full Stack Development with Go is a comprehensive guide that covers all aspects of full-stack ...